Trends in the bushmeat market trade in North Sulawesi and conservation implications. (31st August 2021) - Bailey, C.; Hilser, H.; Siwi, Y.; Lawe, Z.; Waterman, J.; Loffeld, T. A. C.; Sampson, H.; Tasirin, J.; Melfi, V.; Bowkett, A. E.
Abstract: The bushmeat trade, or the trade in wild animals for meat, is a primary threat to wildlife and ecosystems in Sulawesi, Indonesia. Hunting for trade and consumption can hasten the local extirpation of vulnerable species, such as fruit bats and the protected babirusa and Sulawesi crested black macaque. This study provides a much‐needed step in understanding the bushmeat trade by describing longitudinal trends in the amount of bushmeat (animal carcasses) observed for sale in markets in North Sulawesi, a particularly biodiversity‐rich area. Surveys were conducted in 10 markets in 2011, 2015, 2018 and 2019. At each market, total counts of all taxa for sale were noted, and encounter rates per market sample were derived to account for variable sampling effort across years and markets. Generalized Linear Mixed Models were used to compare encounter rates across years, months and markets. Our results show that although animal carcasses are still sold in high numbers, there has been an overall decrease between 2011 and 2019, particularly between 2011 and 2018 (encounter rate fell by 99%). However, bats, rats and Sulawesi warty pigs were still present at high levels, indicating a persistent demand for bushmeat in North Sulawesi. The encounter rate of protected taxa for sale was low, but steady throughout the study period. We identified which markets sold the greatest amount of bushmeat to inform future conservation actions and management. Based on our results, the persistent demand for bushmeat in the region, and the continued presence of protected taxa in the markets, we recommend further research to establish the sustainability of the bushmeat trade at its current rate. Abstract : The bushmeat trade is a primary threat to wildlife and ecosystems in Sulawesi, Indonesia. This study provides a much‐needed step in understanding the bushmeat trade by describing longitudinal trends in the amount of bushmeat observed for sale in markets in North Sulawesi. Our results show that although animal carcasses were still sold in high numbers, there was an overall decrease between 2011 and 2019. However, bats, rats and Sulawesi warty pigs were still present at high levels, indicating a persistent demand for bushmeat in North Sulawesi. The photo credit is 'Andrew Walmsley Photography, Selamatkan Yaki'.